Constructing Dissolution–Resistant Interphases for Long‐Life Sodium‐Ion Batteries at Elevated Temperatures - Wenting Deng; Xiaofan Du; Gaojie Xu; Shitao Wang; Li Du; Tiantian Dong; Rongxian Wu; Chuanchuan Li; Zhaolin Lv; Jiangwei Ju; Xinhong Zhou; Guanglei Cui (Advanced Science, 2025)
Abstract Rechargeable sodium‐ion batteries (SIBs) utilizing NaPF6‐carbonate electrolytes consistently exhibit unsatisfactory cycle life at elevated temperatures, posing a significant challenge for their large‐scale commercialization. This is mainly caused by the instability of interphase layers at elevated temperatures, especially the high solubility of interphase components (especially NaF) in carbonate solvents. In this study, a novel additive of sodium difluorobis(oxalato) phosphate (NaDFBOP) is synthesized and introduced into NaPF6‐carbonate electrolytes to enhance the cycle life of commercial SIBs composed of NaNi1/3Fe1/3Mn1/3O2 (NFM) cathode and hard carbon (HC) anode, particularly at 50 °C. Specifically, the NaDFBOP enables NFM/HC SIBs to retain 85.45% of initial capacity after 1000 cycles at 30 °C and 90.76% after 500 cycles at 50 °C. Theoretical calculations reveal that DFBOP⁻ anions enter the first solvation shell of Na+, and NaDFBOP exhibits a strong propensity for decomposition. Characterizations suggest that NaDFBOP favors the formation of dissolution–resistant robust interphase layers enriched of dissolution‐resistant oxalate‐containing species and inorganic NaF, which have strong mutual binding energy. This work underscores the critical importance of designing functional additives and constructing dissolution‐resistant robust interphases to enhance the elevated temperature cycle life of SIBs.